Lower Lip Reanimation: Experience Using the Anterior Belly of Digastric Muscle in 2-stage Procedure. Issue 3 (March 2021) - Tzafetta, Kallirroi; Ruston, Julia C.; Pinto-Lopes, Rui; Mabvuure, Nigel Tapiwa
Abstract : Background: Lower lip depression was historically regarded a neglected area of facial paralysis, but, with refinement of techniques, has gained increasing attention. We present the first detailed description and evaluation of a 2-stage technique, using first cross facial nerve graft and then the anterior belly of digastric muscle (ABDM), innervated by the cross facial nerve graft, to restore dynamic and spontaneous lower lip depression. Methods: Retrospective analysis of 2-stage lower lip reanimations between 2010 and 2018 was performed. Demographics, etiology, and operative details were recorded. Videos were graded pre/postoperatively using a 5-point Likert scale by 21 independent observers. Objective changes of symmetry were analyzed using Photogrammetry (Emotrics). Results: Twenty-seven patients were identified (median age 34.9 years, range 6–64). The mean duration between the 2 stages was 15.1 months. Follow-up ranged from 18–72 months. There were minor complications in 4 patients, and 1 case was abandoned due to insufficient length of anterior belly of digastric muscle. Average peer-reviewed scores improved from 2.1 to 3.2 ( P < 0.05). Emotrics did not show improvement in static symmetry ( P > 0.05). However, during open-lip smiling, lower lip height improved significantly ( P < 0.05) whilst dental show improvements approached significance ( P < 0.08). Lower lip symmetry was also improved during lower lip depression, as shown by improvements in lower lip height ( P < 0.05), smile angle, and dental show (both P < 0.05). Conclusions: These results show the safety and efficacy of 2-stage lower lip reanimation using anterior belly of digastric muscle transposition. This procedure is our choice for longstanding lower lip paralysis and provides coordinated spontaneous lower lip depression, thus enhancing the overall perioral animation and smile. Abstract : Supplemental Digital Content is available in the text.